Crowdfunding Platform Mechanisms: Mitigating Fraud and Enhancing Campaign Success - Ben Najee, Abdussalam (Université d'Ottawa | University of Ottawa, 2026)
The purpose of this thesis is to explore the role of crowdfunding platforms in protecting investors by investigating the platform governance mechanisms (PGMs) they have implemented to determine their effectiveness in increasing campaign success and reducing fraudulent activities. The specific objectives are (i) to know the prevalence of governance mechanisms implemented by crowdfunding platforms, (ii) to evaluate the effectiveness of PGMs in protecting investors against suspended campaigns on crowdfunding platforms, and (iii) to compare the PGMS of different types of crowdfunding platforms to identify any differences and potential best practices. The data collection method consists of two types of platforms: reward-based crowdfunding that covers the years between 2009 and 2023, and equity-based crowdfunding platforms that cover the years between 2018 and 2021, as well as the PGMs applied to both types. Using a logistic regression model, the general findings suggest that mechanisms such as social media and Google Analytics have mixed effects. Social media positively influences campaign success on equity-based campaigns but negatively affects campaign success on reward-based campaigns. In contrast, google analytics substantially influence reward-based campaigns positively, while having a negative effect on equity-based campaigns. The third-party verification mechanism was ineffective in campaigns to succeed or reduce fraud. In addition, the number of funders and amount pledged can enhance the successful campaigns, while they cannot distinguish between fraudulent and non-fraudulent campaigns. The duration is mixed with longer duration enhancing campaign success and shorter duration reducing fraud for reward campaigns. However, for equity-based campaigns, a shorter duration enhances campaign success. The study contributes valuable research knowledge by showing the role of crowdfunding platforms in protecting investors and increasing campaign success. The results indicate the necessity for further economic research on PGMs to enhance the campaign's success and prevent fraud, as well as highlight other essential topics for future study.
Keywords: Crowdfunding platforms; success; fraud; PGMs